Revealing Genomic Profile That Underlies Tropism of Myeloma Cells Using Whole Exome Sequencing - Youngil Koh; Daeyoon Kim; Woo-June Jung; Kwang-Sung Ahn; Sung-Soo Yoon (International Journal of Genomics)
Background. Previously we established two cell lines (SNU_MM1393_BM and SNU_MM1393_SC) from different tissues (bone marrow and subcutis) of mice which were injected with single patient’s myeloma sample. We tried to define genetic changes specific for each cell line using whole exome sequencing (WES). Materials and Methods. We extracted DNA from SNU_MM1393_BM and SNU_MM1393_SC and performed WES. For single nucleotide variants (SNV) calling, we used Varscan2. Annotation of mutation was performed using ANNOVAR. Results. When calling of somatic mutations was performed, 68 genes were nonsynonymously mutated only in SNU_MM1393_SC, while 136 genes were nonsynonymously mutated only in SNU_MM1393_BM. KIAA1199, FRY, AP3B2, and OPTC were representative genes specifically mutated in SNU_MM1393_SC. When comparison analysis was performed using TCGA data, mutational pattern of SNU_MM1393_SC resembled that of melanoma mostly. Pathway analysis using KEGG database showed that mutated genes specific of SNU_MM1393_BM were related to differentiation, while those of SNU_MM1393_SC were related to tumorigenesis. Conclusion. We found out genetic changes that underlie tropism of myeloma cells using WES. Genetic signature of cutaneous plasmacytoma shares that of melanoma implying common mechanism for skin tropism. KIAA1199, FRY, AP3B2, and OPTC are candidate genes for skin tropism of cancers.